Design of an intelligent car air conditioning louver for efficient cooling of car interior compartment / Dick Chang Jai Hau - Dick Chang, Jia Hau (2021)
The increase of car usage in the current century seeks for more comfort in the car even the back passengers. Major characteristics passengers look for are the air flow from the louver. Louvers require to be adjusted manually by the front passengers and maybe dangerous for driver to adjust when they are only passenger in the car. Previous research found primarily improving or adjusting the components air supplies before entering the louvers. However, this still unable to direct the air flow to the desired locations. In this research, with the integration of Solidworks and Ansys Fluent application, I was able to simulate the situation of air flow occur in the car. By creating the body structure of a car, the cavity model was extracted along with the parallel position of the louver. Results were obtained and based on that, the louver is adjusted to fulfill desire location for one to four passengers respectively. As for the louvers, it is designed to be integrated with servo motor, microprocessor, and infrared sensors. As the infrared sensor triggered by the passenger through wearing the seat belt, the signal will send to the microprocessor and transfer desired output signals based on the completed simulations. Having the intelligent louver that auto-adjust based on the number of passengers a car removes the hectic for the passengers to adjust them manually.